Strategies For Acting Preschool Teachers In Preparing The Paud Transition To Primary School Level Through Literacy Movement - Masturoh, Umi; Noorhayati, Siti Mahmudah; Widyaningrum, Novita; Wulandari, Fitrianti (LPPM, STAI Al-Azhar Menganti, 2024)
Literacy culture is very important to be driven together to improve the quality of early childhood education in educational units. Literacy is not only related to children's reading, writing and arithmetic (calistung) abilities, but includes all the abilities within the child himself, these abilities need to be developed as early as possible as literacy is the foundation of children's abilities at a later age. Devotion regarding strategies for assisting PAUD teachers in preparing the transition period for PAUD to SD/MI level through the literacy movement in the South Gresik region using the ABCD (Asset Based Community Development) strategy which is real in educational units. Developing literacy does not mean children are intense and full of discipline but to conclude in The main results are (1) analysis of the superiority of PAUD teacher assistance services in preparing the PAUD transition period to SD/MI level through the literacy movement, (2) analysis of PAUD teacher assistance strategies in preparing the PAUD transition period to SD/MI level through the literacy movement, (3 ) analysis of the expectations of the PAUD teacher mentoring service program in preparing the PAUD transition period to the SD/MI level through the literacy movement.